Samorząd terytorialny jako uczestnik komunikacji społecznej - Kowalczyk, Ryszard (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The author considers local government as a participant of social communication, mainly by means of its public communications. He emphasizes two fundamental forms of public communication, formal and informal. He touches upon the political foundations of local gov- ernment information policies, which implement a specific political vision of the authorities. The author concludes by saying that in the field of information policy a unit of local govern- ment cannot be treated as a passive executor of statutory tasks (in their formal and legal as- pects) but should rather be perceived as an active creator that runs its information policies on the basis of its own local policy (the political and legal aspects).
Local government as a participant of social communication
Keywords: samorząd terytorialny; komunikacja społeczna